THE EFFECT OF COMPENSATION ON EMPLOYEE ACHIEVEMENT AT PT. TELEKOMUNIKASI INDONESIA TBK RANTAU PRAPAT - Rida - Kurnia (Movere Journal, 2021)
This study entitled "The Effect of Compensation on Employee Achievement at PT. Telekomunikasi Indonesia Tbk Rantau Prapat". The purpose of this study was to determine whether there is an effect of giving compensation to employee performance at PT.Telekomunikasi Indonesia Tbk Rantau Prapat. The data used in this study is primary data with the research instrument in the form of a questionnaire. The population used is 48 employees at PT. Telekomunikasi Indonesia Tbk Rantau Prapat, using a saturated sample of 48 respondents. The method used in this research is descriptive quantitative method. The data analysis technique used simple linear regression analysis with the regression equation Y = 10,271 + 693 + e. The results obtained in this study showed an R2 value of 59.8% and a t-test of 8.270 so it can be concluded that the provision of compensation has a positive and significant effect on employee achievement at PT.Telekomunikasi Indonesia Tbk Rantau Prapat, the remaining 40.2% is influenced by other factors.